Pengaruh Leader-Member Exchange dan Motivasi Intrinsik terhadap Komitmen Organisasional pada UMKM Konveksi Pakaian - Megarani, Shifa; Dewi, Misthika; Wahyu Utami, Windyta (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine LMX and intrinsic motivation to organizational commitment in UMKM Konveksi Pakaian in Kebumen. This study involved 50 employees as responses and data were taken by census. The results found that LMX and intrinsic motivation significantly affect organizational commitment. The implication is that leaders can strengthen the factors that cause organizational commitment so that it can be evaluated and renewed in the organization.